2016
DOI: 10.1002/pd.4911
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cavum septi pellucidi in fetuses with microdeletion 22q11

Abstract: The CSP is a structure routinely evaluated in screening ultrasound. A wide CSP is found in second trimester fetuses with del. 22q11. A dilated CSP may be an important sonographic marker for the presence of del. 22q11 along with conotruncal malformations and thymic hypoplasia. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…Only less than 4% of children at the age of 1 year still have the CSP visible on computed tomography . A persistent CSP has been associated with traumatic brain injury and schizophrenia Prenatally, an enlarged CSP has been associated with chromosomal anomalies, including trisomy 21, 18, and 13, as well as 22q11 microdeletion . An abnormally shaped wide and short CSP with a decreased CSP length‐to‐width ratio was also found to be associated with fetal partial agenesis of the corpus callosum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only less than 4% of children at the age of 1 year still have the CSP visible on computed tomography . A persistent CSP has been associated with traumatic brain injury and schizophrenia Prenatally, an enlarged CSP has been associated with chromosomal anomalies, including trisomy 21, 18, and 13, as well as 22q11 microdeletion . An abnormally shaped wide and short CSP with a decreased CSP length‐to‐width ratio was also found to be associated with fetal partial agenesis of the corpus callosum .…”
Section: Discussionmentioning
confidence: 99%
“…The former is mostly associated with midline fetal brain abnormalities such as agenesis of the corpus callosum, holoprosencephaly, and septo‐optic dysplasia . The latter has been mostly reported in fetuses with aneuploidies as well as 22q11.2 microdeletion (DeGeorge syndrome) . In fetuses with hypoplastic left heart syndrome (HLHS) and dextro‐transposition of the great arteries ( d ‐TGA), a decreased brain volume secondary to insufficient blood perfusion may cause CSP dilatation by reducing pressure on the CSP.…”
mentioning
confidence: 99%
“…In a study by Serhatlioglu et al, the mean second‐trimester width was 3.1 mm, and the mean anteroposterior diameter was 7.7 mm; the mean third trimester width was 5 mm, and the mean anteroposterior diameter was 11.7 mm. In addition, Chaoui et al reported a linear increase in the cavum septi pellucidi width relative to the biparietal diameter, with mean cavum septi pellucidi widths of 3.0 to 6.3 mm for biparietal diameters of 40 to 90 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An enlarged cavum septi pellucidi has also been reported prenatally in fetuses with 22q11 deletion syndrome. In a study of 37 fetuses with 22q11 deletion syndrome, 67.5% had a dilated cavum septi pellucidi in the second half of gestation . Although further investigations examining the importance of incidental cavum septi pellucidi enlargements and associations with other anomalies are needed, genetic counseling and a discussion of noninvasive and diagnostic prenatal testing should be considered during pregnancy…”
Section: Discussionmentioning
confidence: 99%
“…Even when the CSP is present, its size and shape should be assessed for deviations from the norm. A CSP with a large width may indicate an increased risk of numeric or structural chromosomal abnormality . An abnormal ratio of the CSP length and width is considered to be an indirect sign of partial agenesis of the corpus callosum (pACC) .…”
Section: Introductionmentioning
confidence: 99%